2009
DOI: 10.1111/j.1751-0813.2009.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Wounds of the pastern and foot region managed with phalangeal casts: 50 cases in 49 horses (1995–2006)

Abstract: In this study, wounds involving the pastern and foot that were treated with a phalangeal cast carried a good prognosis for soundness (89.4%) and cosmetic healing (89.5%). The phalangeal casts were well-tolerated and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In the small case series from Booth and Knottenbelt (1999), 50 % of the lacerations were sutured, although the reason for this is not stated in the paper. In a similar publication from Ketzner et al (2009), 63.6% of wounds were sutured and the authors found no significant difference in outcome between cases involving or not involving a synovial structure. In a more recent publication on wounds of the lower limb Eggleston (2018), recommends that a wound communicating with a synovial structure be managed with replaceable bandages until it can be confirmed that synovial communication is sealed and the infection resolved.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 90%
See 2 more Smart Citations
“…In the small case series from Booth and Knottenbelt (1999), 50 % of the lacerations were sutured, although the reason for this is not stated in the paper. In a similar publication from Ketzner et al (2009), 63.6% of wounds were sutured and the authors found no significant difference in outcome between cases involving or not involving a synovial structure. In a more recent publication on wounds of the lower limb Eggleston (2018), recommends that a wound communicating with a synovial structure be managed with replaceable bandages until it can be confirmed that synovial communication is sealed and the infection resolved.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 90%
“…Of the 61 horses available at follow-up in the Janicek et al (2005) study, 18% developed a hoof wall defect, but the number of horses treated with a foot cast compared to bandaging alone or a combination of the two is not stated. In the study from Ketzner et al (2009), 10.5% of all wounds healed with excessive scarring at the coronary band and hoof. As previously mentioned, all horses in that cases series were treated with casting and the number of wounds involving the coronary band/hoof remains unclear.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this study of 50 wounds in 49 horses, treatment consisted of wound debridement, lavage, wound closure (in 28 wounds), cast application and antibiotics (in 84% of cases). 6 The authors report that applying the cast was easy with the horses either standing or under general anaesthetic and there were minimal complications. At follow-up, the majority of horses were sound, three horses were still lame, one was euthanased because of persistent lameness and another three horses were lost to follow-up.…”
Section: Phalangeal Casts Well-tolerated and Effective For Equine Foomentioning
confidence: 99%
“…Alignment and apposition of the coronary band is most important to the outcome (Stashak 1989). In a retrospective study, wounds involving the pastern and foot that were treated with a phalangeal cast carried a good prognosis for soundness and cosmetic healing (Ketzner et al 2009). When the DIP joint is involved, arthrodesis may sometimes be performed to stabilize the joint as a salvage procedure if infection is not present (Reeves et al 1989).…”
Section: Discussionmentioning
confidence: 99%